Urgensi Integrasi Ilmu Dan Agama - Mohamad Ghozi (Pena Islam Jurnal Pendidikan Agama Islam, 2021)
Religion without knowledge will be lame, while knowledge without religion will be blind. Religion not only emphasizes the relationship between humans and the creator, but also human relations between humans. In fact, because of the many religious relationships with fellow humans that it is regulated in a religious principle called muammalah. Because of this need, it is necessary to have a social science with Islamic nuances, so that humans can maximize themselves more or humanize humans. More deeply in this all-sophisticated, modern world, where many humans deify reason and science, religion has a significant role. In the view of Islam, science may develop as high as the sky and as wide as the horizon, but it should not conflict with religious principles.